Willingness-to-pay for road safety improvement. (May 2016) - Haddak, Mohamed Mouloud; Lefèvre, Marie; Havet, Nathalie
Highlights: This study evaluates the willingness-to-pay (WTP) for road safety improvement. We focus on non-fatal injuries caused by road traffic accidents. Severity of injury appears to be a decisive factor in WTP. A direct or indirect accident experience significantly increases WTP. WTP tends to remain invariant regardless of the degree of risk reduction. Abstract: Few studies have explored, to date, the issue of the monetary valuation of non-fatal injuries caused by road traffic accidents. The present paper seeks to raise interest in this question and to estimate, by contingent valuation, French households' willingness-to-pay (WTP) to improve their road safety level and reduce their risk of non-fatal injuries following a road accident. More precisely, a Tobit and a type-II Tobit model were estimated to identify factors for WTP. The results highlighted the significant positive influence of injury severity on WTP. Experience of road traffic accidents seemed to play an important role, positively influencing valuation of non-fatal injury.